The impact of anxiety level on medical decisions of non-COVID patients during the pandemic outbreak. (14th October 2021) - Koren, O; Abu Rajab, S; Barbour, M; Shachar, M; Shahar, A; Zubidat, K; Slim, W; Igbariya, D; Rozner, E; Turgeman, Y; Mader, E
Abstract: Background: High anxiety levels (HAL) were widely reported in patients during the COVID outbreak. We assess whether HAL influenced medical decision-making (MDM) of Non-COVID patients. Method: We prospectively recruited patients with cardiovascular complaints during February and September 2020. We assessed anxiety levels using the GAD-7, Beck Inventory, the cardiac anxiety questionnaires, and a newly designed MDM questionnaire. Results: We recruit 287 patients. The mean age was 52.6±14.9 (females represent 36.2%). HAL was reported in 261 (90.3) patients and was more prevalent in old (p<0.001 for all questionnaires), married, and unemployed patients (significant p-value for all). Cardiovascular comorbidities and a history of anxiety, depression, and psychiatric disorder were independent factors for HAL (p<0.001 for all). Coronary catheterization was performed more in HAL (p<0.001 for all), yet the rate of significant coronary artery disease was lower than in patients with low anxiety level (LAL) (p<0.001 for all). 161 (56.9) patients reported that their MDM was affected (<0.001), and 149 (76.8) patients indicated that they would have gone earlier to the hospital if not the pandemic (p=0.03 for high DM-19 score). Patients with HAL seek medical care longer than LAL patients (p=0.02). Correlation analysis revealed a positive correlation between MDM and HAL (p<0.001 for all). Conclusion: Our study shows a strong and positive correlation between anxiety level and MDM. Old patients with cardiovascular comorbidities and a history of mental disorders were at particularly high risk for HAL and sought medical treatment significantly longer than LAL patients. Funding Acknowledgement: Type of funding sources: None.